Development of Hydrophilic Interaction Liquid Chromatography Method for the Analysis of Moxonidine and Its Impurities - Slavica Filipic; Milica Elek; Marija Popović; Katarina Nikolic; Danica Agbaba (Journal of Analytical Methods in Chemistry)
Fast and simple hydrophilic interaction liquid chromatography (HILIC) method was developed and validated for the analysis of moxonidine and its four impurities (A, B, C, and D) in pharmaceutical dosage form. All experiments were performed on the Agilent Technologies 1200 high-performance liquid chromatography (HPLC) system using Zorbax RX-SIL, 250 mm × 4.6 mm, 5 μm column as stationary phase (T=25°C, F=1 mL/min, and λ=255 nm), and mixture of acetonitrile and 40 mM ammonium formate buffer (pH 2.8) 80 : 20 (v/v) as mobile phase. Under the optimal chromatographic conditions, selected by central composite design, separation and analysis of moxonidine and its four impurities are enabled within 12 minutes. Validation of the method was conducted in accordance with ICH guidelines. Based on the obtained results selectivity, linearity (r≥0.9976), accuracy (recovery: 93.66%–114.08%), precision (RSD: 0.56%–2.55%), and robustness of the method were confirmed. The obtained values of the limit of detection and quantification revealed that the method can be used for determination of impurities levels below 0.1%. Validated method was applied for determination of moxonidine and its impurities in commercially available tablet formulation. Obtained results confirmed that validated method is fast, simple, and reliable for analysis of moxonidine and its impurities in tablets.